Kissing doorknobs - Hesser, Terry Spencer (New York : Delacorte Press, 1998)
Fourteen-year-old Tara describes how her increasingly strange compulsions begin to take over her life and affect her relationships with her family and friends.
In her first novel, Kissing Doorknobs, Terry Spencer Hesser has written an inspiring, often humorous novel about Obsessive Compulsive Disorder, a topic that merits discussion and compassion
Keywords: Obsessive-compulsive disorder -- Fiction; Mental illness -- Fiction; Family life -- Fiction; Friendship -- Fiction